AKUT İSKEMİK STROKTA SERUM NÖRON-SPESİFİK ENOLAZ’IN PROGNOSTİK DEĞERİ - BULUT, Serpil; BERİLGEN, M. Said; DOLU, Yücel; MÜNGEN, Bülent (Cerrahpaşa Medical Journal, 2019)
Background.- The aim of the study was to see whether the serum neuron specific enolase (NSE) levels, as a noninvasive technique could be utilized to determine the morbidity at early stage after acute ischemic stroke. Design.- In the present study, 40 patients with acute ischemic stroke and 20 ages and gender matched volunteer were investigated. Serum NSE levels at 48th hours, fifth days, and tenth days were analyzed and simultaneous clinical status according to Scandinavian stroke scale was examined and infarct volumes at 48th hours were measured. Results and Conclusion.- There was a statistically significant difference in serum NSE values at 48th hours and fifth days of whole patient group (22,51±7.05 ng/ml, 13,1±4,76 ng/ml, respectively) compared to those of control group (8.54±2,58 ng/ml), ( p<0.001, p<0.01, respectively). However there was no statistically significant difference between the patients and controls at 10 days (p<0.01). So, it was thought that NSE had 94% sensitivity and 80% specifity for acute ischemic stroke. There were positive correlation among NSE levels and infarct volumes, and negative correlation among NSE levels and clinical status.